2013
DOI: 10.1021/es403110b
|View full text |Cite
|
Sign up to set email alerts
|

Emission Characteristics for Polycyclic Aromatic Hydrocarbons from Solid Fuels Burned in Domestic Stoves in Rural China

Abstract: Emission characterization of polycyclic aromatic hydrocarbons (PAHs) from residential combustion of crop residues, woody material, coal, and biomass pellets in domestic stoves in rural China are compared in term of emission factors (EFs), influencing factors, composition profiles, isomer ratios and phase distributions. The EFs of PAHs vary by two orders of magnitude among fuel types suggesting that a detailed fuel categorization is useful in the development of an emission inventory and potential in emission ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(58 citation statements)
references
References 102 publications
(288 reference statements)
6
51
1
Order By: Relevance
“…The factors, which can affect the coal combustion, can also influence the emissions of pPAHs and oPAHs, including different coal properties, coal shapes, stove types, and air supply (Shen et al, 2013a).…”
Section: Factors Affecting Efs Of Ppahs and Opahsmentioning
confidence: 99%
See 2 more Smart Citations
“…The factors, which can affect the coal combustion, can also influence the emissions of pPAHs and oPAHs, including different coal properties, coal shapes, stove types, and air supply (Shen et al, 2013a).…”
Section: Factors Affecting Efs Of Ppahs and Opahsmentioning
confidence: 99%
“…Chen et al (Chen et al, 2005) studied the impact of geological maturity to the emission factors (EFs) of PAHs from coal combustion and found that the combustion of bituminous coal with vitrinite reflectance (R O , a measure of the geological maturity of coal) around 0.9% produced the highest EFs of particulate matter, elemental carbon, organic carbon, and PAHs. Shen et al (Shen et al, 2013a) studied the influence of volatile matter (VM) content on the emissions of PAHs and found that medium volatile bituminous coal emitted relatively large quantities of PAHs in comparison with low and high volatile bituminous coals. Meanwhile, the studies of Simoneit (Simoneit, 2002) and Shen et al (Shen et al, 2013a) suggested that the fast burning of low moisture biomass fuel forms an oxygen deficient atmosphere yielding high pollutant emissions, whereas the burning of high moisture fuel requires extra energy to vaporize water reducing combustion temperature and efficiency, and hence increased emissions of incomplete combustion products, such as PAHs and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of RET and COR detection in soil samples indicated that fuel combustion and vehicle emissions contributed considerably to PAHs in the soil (Appendix A4). PAH isomer ratios and principal component analysis (PCA) are both widely used in PAH source apportionment (Dai et al, 2008;Liu et al, 2012;Shen et al, 2013a). A detailed discussion was provided in the appendix (A4).…”
Section: Soil Pahsmentioning
confidence: 99%
“…In Katowice the mean concentrations were equal to 1.7 and 2.6 ng·m -3 , and in Sosnowiec -1.8 and 2.4 ng·m -3 , respectively. In Kraków, during the heating season PAHs and NPAHs, especially chrysene, benzo[a]pyrene or 9-nitroanthracene, are mainly emitted during the combustion of coal, wastes or biomass in domestic stoves [18,19]. Traffic-related pollutions are another factor which influence the increase of these organic compounds amount.…”
Section: Resultsmentioning
confidence: 99%